Over-Expression of Arabidopsis EDT1 Gene Confers Drought Tolerance in Alfalfa (Medicago sativa L.) - Zheng, Guangshun; Fan, Cunying; Di, Shaokang; Wang, Xuemin; Xiang, Chengbin; Pang, Yongzhen (Frontiers in Plant Science, 2017)
Alfalfa (Medicago sativa L.) is an important legume forage crop with great economic value. However, as the growth of alfalfa is seriously affected by an inadequate supply of water, drought is probably the major abiotic environmental factor that most severely affects alfalfa production worldwide. In an effort to enhance alfalfa drought tolerance, we transformed the Arabidopsis Enhanced Drought Tolerance 1 (AtEDT1) gene into alfalfa via Agrobacterium-mediated transformation. Compared with wild type plants, drought stress treatment resulted in higher survival rates and biomass, but reduced water loss rates in the transgenic plants. Furthermore, transgenic alfalfa plants had increased stomatal size, but reduced stomatal density, and these stomatal changes contributed greatly to reduced water loss from leaves. Importantly, transgenic alfalfa plants exhibited larger root systems with larger root lengths, root weight and root diameters than wild type plants. The transgenic alfalfa plants had reduced membrane permeability and malondialdehyde content, but higher soluble sugar and proline content, higher SOD activity, higher chlorophyll content, enhanced expression of drought-responsive genes, as compared with wild type plants. Notably, transgenic alfalfa plants grew better in a two-year field trial and showed enhanced growth performance with increased biomass yield. All of our morphological, physiological and molecular analyses demonstrated that the ectopic expression of AtEDT1 improved growth and enhanced drought tolerance in alfalfa. Our study provides alfalfa germplasm for use in forage improvement programs, and may help to increase alfalfa production in arid lands.